Referral Pattern of Patients to Psychiatry Department at Neuroscience Institute in Bangladesh - Uddin, MM Jalal; Chowdhury, MS Jahirul Hoque; Islam, Md Jahidul; Chowdhury, Tauhidul Islam; Baqui, Morshed; Sarker, Poritosh Kumar; Kabir, AKM Golam; Alam, M Badrul; Mohammad, Quazi Deen (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: Significant proportion of psychiatric illnesses has been reported in neurology inpatients and outpatients. Objective: The purpose of the present study was to find out the referral pattern of patients to psychiatry department from different departments of National Institute of Neurosciences and Hospital (NINS&H) and to make diagnosis of referred patients. Methodology: This descriptive cross sectional study was done in psychiatry department at NINS&H, Dhaka from July 2013 to December 2013. Patients referred to psychiatry department from different outpatients and inpatients departments were taken as study population. Psychiatric diagnoses of the patients were done by the psychiatrist following Diagnostic and Statistical Manual of Mental Disorders-IV-Text Revision (DSM-IV-TR) diagnostic criteria. Semi structured questionnaire was used to collect socio-demographic data. Ethical issues were maintained strictly. Results: A total number of 477 patients were referred to psychiatry department. Most of the patients 469 (98.32%) were referred from outpatients department and only 8(1.68%) from inpatients department. Among the referred patients 97.28% had psychiatric illness. The commonest psychiatric diagnosis were somatoform disorders 156(32.70%), anxiety disorders 66(13.83%), major depressive disorder 95(19.91%), bipolar mood disorder 27(5.66%), schizophrenia and related disorders 33(6.92%). Next common diagnosis were substance related disorder 18(3.77%), epilepsy 14(2.94%), mental retardation 13(2.73%), autism 10(2.10%), attention deficit hyperactivity disorder 9(1.89%), sleep disorder 9(1.89%). Conclusion: In conclusion there is a large number of psychiatric patients attended at the OPD as well as the IPD of the referral neurological tertiary care hospital of which somatoform disorders is the most commonly found. J. Natl Inst. Neurosci Bangladesh 2015;1(1):8-11